Clozapine augmented with aripiprazole in 5 patients with schizophrenia - Abu-Tair, Fatima; Kopitz, Jürgen; Bergemann, Niels (Journal of clinical psychopharmacology, 2006)
An abstract is unavailable.
Gesehen am 15.12.2020